Consumer's perceptions and motivations on the consumption of fortified foods and 3D food printing - Frederica Silva; Tatiana Pereira; Susana Mendes; Leonel Gordo; Maria Manuel Gil (Future Foods)
Consumer attitudes and acceptance of emerging technologies in the food sector, as well as their application, are determining factors for their successful implementation. In this study, a survey was conducted in order to better know and understand the perception, motivation and consumption associated with fortified foods and 3DPF (3-Dimensional Printing Food). Key points such as food neophobia and factors involved in the opinion forming process towards 3DPF were included in the questionnaire (namely, perceived benefits, willingness to consume, food engagement, preference for familiar foods and affinity with digital tools). The results showed that the gender influences the knowledge in 3D printing as a technology and that 51.6 % of consumers are willing to try 3DPF. Consumers who want healthy food adapted to their needs are also more receptive to foods produced on 3D printers. 54.1 % of consumers indicate that if 3DPF were nutritionally richer than an equal and/or existing product on the market, they would be willing to buy it. Respondents also mentioned fruit and vegetable by-products and fish with no commercial value as the most suitable raw materials for 3D printing. Thus, it can be concluded that there is a clear motivation to try 3DPF, providing an opportunity for their inclusion in the future food chain.